Luis I. PRÁDANOS, "Postgrowth Imaginaries: New Ecologies and Counterhegemonic Culture in Post-2008 Spain". Liverpool, Liverpool University Press, 2018, 240 pp. - Marrero Henríquez, José Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Review of Luis I. Prádanos, Postgrowth Imaginaries: New Ecologies and Counterhegemonic Culture in Post-2008 Spain. Liverpool, Liverpool University Press, 2018, 240 pp.
Keywords: Postgrowth Imaginaries; Spanish Culture; Ecocriticism; New Ecologies; Postcarbon Societies